Understanding the challenges related to breastfeeding education and barriers to curricular change: a systems perspective for transforming health professions education - Michaud-Létourneau, Isabelle; Gayard, Marion; Lauzière, Julie; Beaudry, Micheline; Pascual, Laura Rosa; Chartier, Isabelle; Herzhaft-LeRoy, Juliette; Chiasson, Sylvie; Fontaine-Bisson, Bénédicte; Pound, Catherine; Gaboury, Isabelle (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Objectives: A majority of women and families wish that their babies be breastfed. However, too many still receive insufficient or inappropriate initial care from health professionals (HPs) who have limited breastfeeding (BF) competencies. We investigated barriers and potential solutions to improve the undergraduate training programs for various HPs.Methods: Focus groups were carried out in three universities in Quebec and one in Ontario (Canada), with 30 faculty and program directors from medicine, midwifery, nursing, nutrition, and pharmacy. Discussions were subjected to thematic content analysis, before being validated in a strategic planning workshop with 48 participants from the same disciplines, plus dentistry and chiropractic.Findings: Substantive improvements of undergraduate training programs for BF could be obtained by addressing challenges related to the insufficient, or lack of, (i) interactions among various HPs, (ii) opportunities for practical learning, (iii) specific standards to guide course content, (iv) real-life experience with counselling, and (v) understanding of the influence of attitudes on professional practice. Several potential solutions were proposed and validated. The re-interpretation of the results in light of various literature led to an emerging framework that takes a systems perspective for enhancing the education of HPs on BF.Conclusions: To improve the education of HPs so as to enable them to provide relevant support for future mothers, mothers and their families, solutions need to be carried out to address challenges in the health system, the education system as well as regarding the curricular change process.